Analisis dan Perancangan Aplikasi Sistem Informasi Akuntansi Pembelian dan Penjualan Roti Bakar Menggunakan Microsoft Access 2019 (Studi Kasus Pada UMKM “Roti Bakar Batas Kota”) - Furi Fatwa Dini; Sugih Sutrisno Putra; Darya Setia Nugraha; Sudjana; Jouzar Farouq Ishak (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
In the era of increasing technological development, business unit owners are increasingly motivated to strengthen their competitiveness. Roti Bakar Batas Kota is a home-based business unit that produces and sells toast with various flavors. During the business, there are several obstacles such as the absence of recording purchase transactions, recording sales using Microsoft Excel which is less efficient, and the absence of applications that facilitate recording purchases and sales. The purpose of this study is to determine the purchase and sales information system implemented to produce prototypes of purchase and sales program applications through design using Microsoft Access 2019 software. This applied research was conducted with qualitative methods and used the SDLC (Software Development Life Cycle) method as an analytical tool. With the design of this application, the result obtained is that Roti Bakar Batas Kota can be easier to record transactions, print proof of transactions, and make purchase reports, sales reports, production reports, and raw material inventory reports.